2022
DOI: 10.1289/ehp9808
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Azoxystrobin Fungicide and Metabolite Azoxystrobin-Acid in Pregnant Women and Children, Estimation of Daily Intake, and Evaluation of Placental and Lactational Transfer in Mice

Abstract: Background: Azoxystrobin (AZ) is a broad-spectrum strobilurin fungicide that is used in agriculture and was recently added to mold- and mildew-resistant wallboards. AZ was found to have toxic effects in animals at embryonic stages and was listed as a frontline target for biomonitoring in children. Objectives: This study investigated exposure to AZ in pregnant women and young children, whether AZ could be transferred from an exposed mother to offspring, and whether AZ or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…For example, Paenibacillus was positively correlated with the temperature, consistent with the literature that members of Paenibacillus are heat resistant and grow well in warmer temperatures ( Kaur et al 2018 ). Azoxystrobin, ethylparaben, and captan are fungicides or antifungal agents ( Rodrigues et al 2013 ; European Food Safety Authority [EFSA] et al 2020 ; Hu et al 2022 ) that negatively correlated with different fungi ( Fig. 2 F).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Paenibacillus was positively correlated with the temperature, consistent with the literature that members of Paenibacillus are heat resistant and grow well in warmer temperatures ( Kaur et al 2018 ). Azoxystrobin, ethylparaben, and captan are fungicides or antifungal agents ( Rodrigues et al 2013 ; European Food Safety Authority [EFSA] et al 2020 ; Hu et al 2022 ) that negatively correlated with different fungi ( Fig. 2 F).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the environmental concentrations of AZO had been reported as high as 34 μg/L in river water in Shanghai, China . In particular, a recent study found that AZO’s metabolite AZO-acid was detected in the urine of pregnant women and children in the United States . Over the past decade, the adverse effects of AZO on environmental organisms have received increasing attention. AZO exposure could significantly reduce egg production and fertilization rate, resulting in sex-dependent reproductive toxicity in adult zebrafish (Danio rerio) .…”
Section: Introductionmentioning
confidence: 99%
“…However, a large part of signaling systems is covered already by the recent development of neural network formation assays (Frank et al, 2017;Nimtz et al, 2020). An interesting endpoint to comprehensively capture neuronal differentiation is transcriptome profiling (Pallocca et al, 2016;Shinde et al, 2017;Simon et al, 2019;Dreser et al, 2020;Meisig et al, 2020;Hu et al, 2022). This was exemplified here by the UKN1 assay.…”
Section: The Dnt In Vitro Battery (Ivb)mentioning
confidence: 99%